Learning Experience Concept at Museum Gedung Juang 45 Bekasi Regency as a Digital Museum - Ayu, Jati Paras; Octavanny, Vitha; Hutagaol, Olivia Deliani; Simanjuntak, Melvin Bonardo (Universitas Pendidikan Indonesia, 2023)
ABSTRACTThis study elucidates the digital museum concept and discovers visitors’ learning experiences at Gedung Juang 45 museum, Bekasi district. The method used in this research is descriptive qualitative with a learning process and learning outcome approach to obtain the phenomena' in-depth results. This study aims to show various efforts by museum managers to provide the learning process through interesting and engaging museum activities and various technology provided in the form of, the Digital Map, Interactive Book, Air Wall of the Ancient Sundanese Kingdom, and various interactive media. Moreover, the learning experiences outcomes obtained by visitors are the technology used to produce new knowledge and new abilities in using technology so that they could engage in the learning process. Although it's not too significant in changing behavior, this museum can be a good reference for the learning process for the community so that the purpose of the museum being an engaging educational center can increase knowledge for visitors to become one of the alternative educational tours for Bekasi District. ABSTRAKPenelitian ini mendeskripsikan konsep museum digital dan menemukan pengalaman belajar pengunjung di museum Gedung Juang 45, Kabupaten Bekasi. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif dengan pendekatan proses pembelajaran dan hasil belajar untuk mendapatkan hasil fenomena yang mendalam. Kajian ini bertujuan untuk menunjukkan berbagai upaya pengelola museum dalam menyediakan proses pembelajaran melalui kegiatan museum yang menarik dan menarik serta berbagai teknologi yang disediakan dalam bentuk, Peta Digital, Buku Interaktif, Tembok Udara Kerajaan Sunda Kuno, dan berbagai media interaktif. Selain itu, hasil belajar yang diperoleh pengunjung berupa teknologi yang digunakan untuk menghasilkan pengetahuan baru dan kemampuan baru dalam menggunakan teknologi sehingga dapat terlibat dalam proses pembelajaran. Walaupun tidak terlalu signifikan dalam mengubah perilaku, museum ini dapat menjadi referensi yang baik untuk proses pembelajaran bagi masyarakat sehingga tujuan museum sebagai pusat pendidikan yang menarik dapat menambah pengetahuan bagi pengunjung untuk menjadi salah satu wisata edukasi alternatif bagi daerah Bekasi.